The Limits of Absolute Competence of Religious Courts in Resolving Child Support Disputes Post-Divorce - Mayang Reva Andini; M. Sofyan Alfaraby; Eghi Cipta Adeswhara; M. Abid Agusta; M. Dzikri Firmansyah; Alif Akbar Hamdalah (Yayasan Bina Lentera Insan, 2026)
Divorce does not eliminate the obligation of parents, particularly fathers, to fulfill their children's right to financial support. However, disputes regarding child support after divorce and the limits of the Religious Courts' absolute jurisdiction in resolving such disputes remain common in practice. This study aims to analyze the absolute jurisdiction of the Religious Courts in resolving post-divorce child support disputes and to examine the legal protection of child support rights from the perspectives of Islamic law and Indonesian positive law. This research employs a normative legal research method using statutory and conceptual approaches. Data were collected through library research and analyzed qualitatively using a descriptive-analytical method. The findings indicate that the Religious Courts have absolute jurisdiction to examine, adjudicate, and decide disputes concerning child support rights as part of matrimonial matters. Child support rights are protected under both Islamic law and Indonesian positive law and remain the responsibility of the father even after divorce. Nevertheless, their implementation continues to face various obstacles, including non-compliance by obligated parties, weak enforcement mechanisms, and economic constraints. Therefore, strengthening legal enforcement and optimizing the role of the Religious Courts are necessary to ensure the effective protection and fulfillment of children's support rights.